A Study of Electrical Properties of (PVA-PEG / RB) Composite (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
In this study, (PVA-PEG-RB) composites were fabricated through the casting process with varying amounts of Rhodamine B (RB) dye (0, 1.3, 1.5, 1.7, and 2 wt %). The findings revealed that the dielectric constant and dielectric loss of (PVA-PEG-RB) organic dye composite decrease when the applied electrical field frequency rises, whereas the dielectric loss increases as the organic dye additive concentration increases. The increase in frequency and concentration of the (RB) organic dye both contribute to an increase in the electrical conductivity. From the study the polymeric films have been prepared doped with organic dye have a suitable electrical property that can be using in optical applications such as optical limiting and solar fluorescent concentrates.